PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI PADA PROFITABILITAS LPD - Asri Pramesti, I Gusti Ayu; Budiartha, I Ketut; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
Accounting information system used by Lembaga Perkreditan Desa (LPD) attempt to produce relevant, accurate, and punctually information. The purpose of this research was to prove empirically the effect of quality of accounting information system toward profitability which uncertainty tasks as moderating variable. The population of this research were all LPD operating in Badung Regency in 2012. Sample were selected through proportionate stratified random sampling. While, 94 LPD taken as sample by using of Slovin formula. The respondent were people who directly involved utilizing accounting information system (accounting software). There were 82 questionnaires send back and suitable for analysis. The data were analyzed using Moderating Regression Analysis (MRA). The conclusions of the study are : 1) quality  of accounting information system positively effect toward LPD profitability in Badung Regency, 2) uncertainty tasks as moderating variable weaken the relationship between accounting information system and LPD profitability in Badung Regency.
Keywords: quality of accounting information system, profitability, uncertainty tasks